Feasibility of orbital friction stir welding on clad pipes of API X65 steel and Inconel 625 - Amavisca, Carla V.; Bergmann, Luciano; Lessa, Cleber Rodrigo de Lima; Schroeder, J. G.; Ramos, Fabiano Dornelles; Lemos, Guilherme Vieira Braga; Reguly, Afonso; Klusemann, Benjamin (Medien- und Informationszentrum, Leuphana Universität Lüneburg, 2024)
Orbital friction stir welding (FSW) has been applied to clad pipes, which is certainly of interest to the oil and gas industry. In this context, an FSW system capable of performing sound joints in one pass with full tool penetration was developed. Orbital FSW was executed in 6 mm thick API X65 PSL2 steel clad pipes with 3 mm thick Inconel 625 using a polycrystalline cubic boron nitride (pcBN) tool. The metallurgical and mechanical properties of the joints were investigated. Sound joints with axial forces of 45–50 kN, tool rotational speeds of 400–500 rpm, and a welding speed of 2 mm/s were obtained, illustrating that the developed system can perform FSW joints without volumetric defects.
Keywords: Feasibility; Friction; Metallurgy; Welding